Health professional perceptions about Aids in old age - Oliveira, Isabel Cristina V; Araújo, Ludgleydson F; Saldanha, Ana Alayde W (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the progressive increase in number of HIV/aids cases in old age brings the necessity of studies about the speciaficities in the assistance of this group of people Objective: analyze health professional perceptions about aids in old age, aiming at identifying the aspects that influence in the assistance of serum-positive old patients to HIV/aids. Methods: the sample was constituted by 20 health professionals of different specialities, that assist old patients. To collect the data, a semi-structured interview was used, and was submitted to a thematic content analysis. Results: five thematic categories were arose: aids conception; risks factors; test solicitation; communication of the diagnosis and difficulties in assistance. Weverified the association of aids in old age conceptions to negative themes, such as deception and prejudice and, as the way of infection, medical procedures, such as blood transfusion, and promiscuous sexual behavior. The anti-HIV test solicitation must be done only in cases of characteristic symptomatology of sickness, observing divergences on how to give away the positive diagnosis: whether to communicate it to the patients or to their families. They said they don’t distinguish patients by their soropositivity condition, and so, there are no particular difficulties to this population. Conclusion: conceptions associated to stigmas and prejudices were evidenced, equaling the scientific knowledge to common sense, interfering in their assistance practice. All these questions refer to aids the basis, putting certain contradictions in evidence and determining the main difficulties in the social approach of the patient, showing us that, although the professional teams are instructed in techniques, theory and technology, their comprehension of this phenomenon is restricted to the their specialized knowledge and the action does not take into account in the approach of the patients’ emotional necessities.